Caracterização in vitro e in planta de uma proteína quimérica com atividade antimicrobiana à Ralstonia solanacearum - Morais, Tâmara Prado de (2016)
The phytobacterium Ralstonia solanacearum [(SMITH, 1896) YABUUCHI et al. 1996], causative agent of bacterial wilt and Moko disease, is considered one of the world s most destructive plant pathogen. In Brazil this xylem-restricted bacterium reduces yields of agriculturally important crops and calls for effective disease management strategies, so far limited to preventive actions. Antimicrobial peptides have been considered powerful compounds for plant protection due to their antiviral, antifungal, and antibacterial activities. Hence, they are promising candidates to the development of novel rationally-designed therapies for the control of R. solanacearum. Mirroring the function and properties of cecropin B, a well-studied α-helical antimicrobial peptide (AH-AMP), several candidates were selected by bioinformatic tools and tested in vitro against the bacterium. The identified peptides included a linear AH-AMP within the existing structure of phosphoenolpyruvate carboxylase, named PPC20. This peptide stood out as the most efficient in killing the pathogen without jeopardizing human cells. In order to investigate whether the combination of two innate immune functions provides a robust class of antimicrobial therapeutics, this lytic domain was combined to a putative plant-derived elastase (the pathogenesis-related protein SlP14a), leading to the development of a chimeric protein. To characterize and validate this novel antimicrobial chimera as a biocontrol agent, bioassays were conducted in vitro and in planta. SlP14a and SlP14a-PPC20 were expressed in both bacterial and plant (transient expression) systems. Purified proteins showed in vitro antibacterial activity by inhibiting R. solanacearum growth. In order to explore the in vivo biological function of SlP14a-PPC20, transgenic lines of tomato cultivar MoneyMaker were obtained and characterized. To assess whether these lines acquired enhanced tolerance to the pathogen, they were challenged with R. solanacearum by stem inoculation. The survival rates and the reduction of disease symptoms were significantly higher in transgenic plants compared with the non-transgenic ones. This study proposes an alternative strategy for bacterial wilt control based on expression of a newly designed therapeutic antimicrobial protein in tomato plants.